Where I want to be - DeVito, Cara. (Boston : Houghton Mifflin, 1993)
After the death of her father, fourteen-year-old Kristie gradually sorts out her feelings about her older half brothers with whom she lives in a small Arizona town and about the mother who had left her years ago.
Booklist.
Publisher's Weekly.
School Library Journal.
Young Adult
Keywords: Brothers and sisters -- Fiction; Interpersonal relations -- Fiction; Mothers and daughters -- Fiction; Brothers and sisters -- Fiction; Human relations -- Fiction; Mothers and daughters -- Fiction; Arizona -- Fiction; Arizona -- Fiction